High fructose exposure modifies the amount of adipocyte-secreted microRNAs into extracellular vesicles in supernatants and plasma - Hernández-Díazcouder, Adrián; González-Ramírez, Javier; Giacoman-Martínez, Abraham; Cardoso-Saldaña, Guillermo; Martínez-Martínez, Eduardo; Osorio-Alonso, Horacio; Márquez-Velasco, Ricardo; Sánchez-Gloria, José L.; Juárez-Vicuña, Yaneli; Gonzaga, Guillermo; Sánchez-Lozada, Laura Gabriela; Almanza-Pérez, Julio César; et al. (PeerJ, 2021)
Background High fructose exposure induces metabolic and endocrine responses in adipose tissue. Recent evidence suggests that microRNAs in extracellular vesicles are endocrine signals secreted by adipocytes. Fructose exposure on the secretion of microRNA by tissues and cells is poorly studied. Thus, the aim of this study was to evaluate the effect of fructose exposure on the secretion of selected microRNAs in extracellular vesicles from 3T3-L1 cells and plasma from Wistar rats. Methods 3T3-L1 cells were exposed to 550 µM of fructose or standard media for four days, microRNAs levels were determined in extracellular vesicles of supernatants and cells by RT-qPCR. Wistar rats were exposed to either 20% fructose drink or tap water for eight weeks, microRNAs levels were determined in extracellular vesicles of plasma and adipose tissue by RT-qPCR. Results This study showed that fructose exposure increased the total number of extracellular vesicles released by 3T3-L1 cells (p = 0.0001). The levels of miR-143-5p were increased in extracellular vesicles of 3T3-L1 cells exposed to fructose (p = 0.0286), whereas miR-223-3p levels were reduced (p = 0.0286). Moreover, in plasma-derived extracellular vesicles, miR-143-5p was higher in fructose-fed rats (p = 0.001), whereas miR-223-3p (p = 0.022), miR-342-3p (p = 0.0011), miR-140-5p (p = 0.0129) and miR-146b-5p (p = 0.0245) were lower. Conclusion Fructose exposure modifies the levels of microRNAs in extracellular vesicles in vitro and in vivo. In particular, fructose exposure increases miR-143-5p, while decreases miR-223-3p and miR-342-3p.
Keywords: Fructose; Extracellular Vesicles; Adipocytes; Adipose tissue; microRNA